Clinical characteristics and differential diagnosis model of IgAV with gastrointestinal symptoms and acute abdominal disease: an observational controlled study - Yu Zhang; Yang Liu; Zhiling Li; Wenzhong Niu; Zhixin Zheng; Yuhan Gu (Frontiers in Immunology, 2026)
Background Gastrointestinal symptoms of IgA vasculitis (IgAV) patients are relatively common. These symptoms are similar to those of acute abdomen, coupled with the poor expressive ability of young children and children, which leads to the possibility of misdiagnosis and delayed diagnosis. Methods This is a retrospective observational controlled study. All the patients were treated in Nanyang Central Hospital. The demographic, medical history and laboratory tests data were collected from medical records. The characteristics of patients with IgAV have been described. Based on logistic regression, the diagnostic features of IgAV with abdominal symptoms were identified, and a diagnostic model was established. Results IgAV patients with abdominal symptoms usually have an onset age of over 4 years old and are more common in autumn and winter. Compared with patients with acute abdomen, patients with IgAV have lower indicators related to inflammation and a lower proportion of fever, nausea or vomiting, abdominal distension, and changes in borborygmi. Based on these characteristics, 10 related diagnostic features were identified, and a robust diagnostic model was also established, which may be helpful for clinical diagnosis of IgAV patients. Conclusions The advantage of this study lies in the establishment of a model and nomogram by integrating clinical symptoms and laboratory test data, which has good medical interpretability and clinical practicability.